Factors Implicated in Radiation Therapy Failure and Radiosensitization of Prostate Cancer - Helmut Bonkhoff (Prostate Cancer)
Tissue markers may be helpful in enhancing prediction of radiation therapy (RT) failure of prostate cancer (PCa). Among the various biomarkers tested in Phase III randomized trials conducted by the Radiation Therapy Oncology Group, p16, Ki-67, MDM2, COX-2, and PKA yielded the most robust data in predicting RT failure. Other pathways involved in RT failure are also implicated in the development of castration-resistant PCa, including the hypersensitive androgen receptor, EGFR, VEGF-R, and PI3K/Akt. Most of them are detectable in PCa tissue even at the time of initial diagnosis. Emerging evidence suggests that RT failure of PCa results from a multifactorial and heterogeneous disease process. A number of tissue markers are available to identify patients at high risk to fail RT. Some of these markers have the promise to be targeted by drugs currently available to enhance the efficacy of RT and delay disease progression.